Consequences of Confronting Patronizing Help for People with Disabilities: Do Target Gender and Disability Type Matter?. (17th June 2019) - Wang, Katie; Walker, Keshia; Pietri, Evava; Ashburn‐Nardo, Leslie
Abstract: People with disabilities face a dilemma in dealing with patronizing help: Although accepting unsolicited assistance can incur psychological costs, confronting the helper has been shown to incur interpersonal penalties. The present research explored whether the consequences of confronting patronizing help vary across target gender and disability type. A vignette paradigm introduced participants to various interactions between adults with and without disabilities. Study 1 ( N = 137) showed that, when blind targets confronted help that was clearly patronizing, they were rated as ruder and less warm after (vs. before) confronting regardless of their gender. Study 2 ( N = 368) showed that, although both blind and wheelchair‐using targets were rated as less warm and ruder after (vs. before) confronting, blind targets were penalized more, and patronizing behavior toward blind targets was perceived as more appropriate. These results highlight the importance of considering intersectionality and cross‐disability heterogeneity when examining the multifaceted experience of ableism.